AB1090-HPR Use of Theory in Self-Management Interventions for Exercise and Physical Activity in Adults with Rheumatoid Arthritis. (15th July 2016) - Iversen, M.; Demmelmaier, I.
Abstract : Background: The incorporation of behavioral theories into trials to promote self-management yields positive outcomes. Behavioral theories can inform study design, outcome measure selection and development and influence statistical analyses. However, the persuasiveness of behavioral theory application of exercise/physical activity (PA) trials in rheumatoid arthritis (RA) is limited. Objectives: To identify the use of behavioral theories involving interventions that target exercise and physical activity, determine the most prevalent theories used, and describe how theory was used. Methods: A literature review, searching articles published in English, between 01–01–1980 and 08–12–2015. MEDLINE, Cochrane Central Register of Controlled Trials and CINAHL were searched using the following terms "arthritis, rheumatoid" OR "rheumatoid arthritis" AND exercise [MESH] OR (exercise OR physical activity OR strengthening OR aerobic OR dynamic exercise OR isotonic OR static OR aquatic) AND (theory OR theories OR model OR models) in the title, abstract, or keywords. Inclusion criteria were: (1) published in international academic peer-reviewed journals; (2) evaluated an intervention designed to promote PA behavior; (3) had at least one PA behavior variable as the outcome (4) included adults (≥18 yrs) with RA. Study references and relevant review articles were also checked. Two investigators (ID, MDI) independently selected articles and extracted data using the Theory Coding Scheme (TCS), a standardized 19-item coding tool with good reliability that describes if and how theory informs intervention studies (Michie, 2010). Additional extracted data included: author, publication year, behavioral outcomes (PA and/or exercise), type and duration of intervention, and control group Results: Of 245 articles identified, 45 were duplicates. 200 articles were screened as well as article references. A total of 29 full text articles met inclusion criteria and were reviewed. Of these, 17 were excluded (10 no theory mentioned, 5 were PA studies but were not intervention studies, 1 non-PA intervention and 1 health education evaluation, leaving 12 articles. These 12 studies included 1585 participants, of which 1209 (76%) women. Eleven studies (92%) were randomized controlled trials and 1 was a cohort study. Nine studies (82%) assessed self-management plus exercise and 2 (18%) exercise interventions. Program durations ranged from 5 wks–1 yr. Ten studies (83%) used a single theory. Social Cognitive /Social Learning Theory was the most prevalent theory; 7 studies (58%) linked at least 1 intervention technique to theory, 3 studies (25%) analyzed mediating effects of theoretical constructs, and in 6 studies (50%) results were discussed in relation to the theoretical model. Conclusions: Most theory-based interventions to promote exercise were self-management programs. Social Cognitive/Social Learning Theory was most commonly used in interventions, focusing on self-efficacy, PA/exercise and self-regulation skills. However, only 50% of studies used theory to inform the intervention content and discuss results. We suggest expanding the use of theory throughout the design, evaluation and interpretation of results in intervention studies targeting physical activity in RA. References: Michie S, Prestwich A. Are interventions theory-based? Development of a theory coding scheme. Health Psychol. 2010;29(1):1–8. doi: 10.1037/a0016939. Disclosure of Interest: None declared